Geological Descriptiveness for Specialized Methods in the Investigation of Oriented Core Samples; Understanding the Harmony of the Earth's Resources through Integration of Geosciences - Krasnoshchekova L. A. Lubov Afanasievna (2016, 2016)
Title screen